Peraturan Kepegawaian di Sekretariat Komisi Kejaksaan Republik Indonesia - Johannes Ronald Elyeser Roparulian Hutagalung (SIGn Jurnal Hukum, 2023)
This study aims to examine the normativity of the Non-State Civil Apparatus in supporting the duties and functions of the Attorney Commission and analyze the Secretariat’s personnel normativity based on Ministerial Letter Number B/185/M.SM.02.03/2022. This study uses normative legal research with a statute approach. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the Technical Service Division of the Secretariat provides adequate technical support for addressing the behavior and performance of 28,435 Prosecutors and the Attorney General’s Office personnel. Meanwhile, the existence of six Legal Product Analysts and two Office Administrative Staff as Non-State Civil Apparatus interacting directly with the Technical Service Division of the Secretariat becomes vulnerable due to Ministerial Letter Number B/185/M.SM.02.03/2022. This letter, restricting government personnel professions to only Civil Servants and PPPK, initiates a series of changes in human resource management targeted for completion by November 28, 2023. Therefore, Personnel Development Officers in the Coordinating Ministry and the Head of the Secretariat are recommended to promptly conduct a comprehensive evaluation of personnel structures and functions. Specifically, there need to be concrete steps to balance functional needs, such as increasing the number of personnel in the Secretariat. Furthermore, it is crucial to ensure the personnel transition for six Legal Product Analysts and two Office Administrative Staff so they can continue contributing where their personnel status does not conflict with Ministerial Letter Number B/185/M.SM.02.03/2022. Lastly, it would be prudent to implement a continuous evaluation mechanism, both in the short and long term, to monitor the effectiveness and efficiency of human resource management post-adaptation of the said policy.